Characteristics of Possession of the Ball When the Senior and Preparatory Group Perform the Elements of Children's Soccer (Journal of Pedagogical Inventions and Practices, 2023)
The article presents the results of research work on teaching football elements in preschool instituitons. Moreover, the results of boys and girls doing simple elements of football are compared statistically.